Analysis of the Budget and Realization of Regional Expenditure of the Health Department of the Province of North Sumatra During the Covid-19 Pandemic - M. Farhan Lubis; Oktarini Khamilah Siregar (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This research is entitled "Budget Analysis and Realization of Regional Expenditures for the Health Office of North Sumatra Province during the Covid-19 Pandemic". This study aims to analyze budget control and regional expenditure realization at the North Sumatra Provincial Health Office and prove whether regional budget funds have been realized efficiently. This research was conducted using descriptive research methods. The data collection technique in this study is in the form of documentation, and the data used is secondary data. The results of the research that has been done show that controlling or refocusing regional budget funds at the North Sumatra Provincial Health Office for the 2020 and 2021 Fiscal Years is less effective in increasing the efficiency of budget realization by looking at the ≥ 90% efficiency level of budget realization. This is because the government focuses on controlling and handling Covid-19 through programs to fulfill individual health efforts and public health efforts, programs to increase the capacity of human resources for health, and programs to support provincial government affairs with activities such as conducting outreach to the public about the dangers of Covid-19, by implementing health and vaccination protocols and increasing medical personnel for the prevention and treatment of Covid-19.